Why cultural safety rather than cultural competency is required to achieve health equity: a literature review and recommended definition - Elana Curtis; Rhys Jones; David Tipene-Leach; Curtis Walker; Belinda Loring; Sarah-Jane Paine; Papaarangi Reid (BMC, 2019)
Abstract Background Eliminating indigenous and ethnic health inequities requires addressing the determinants of health inequities which includes institutionalised racism, and ensuring a health care system that delivers appropriate and equitable care. There is growing recognition of the importance of cultural competency and cultural safety at both individual health practitioner and organisational levels to achieve equitable health care. Some jurisdictions have included cultural competency in health professional licensing legislation, health professional accreditation standards, and pre-service and in-service training programmes. However, there are mixed definitions and understandings of cultural competency and cultural safety, and how best to achieve them. Methods A literature review of 59 international articles on the definitions of cultural competency and cultural safety was undertaken. Findings were contextualised to the cultural competency legislation, statements and initiatives present within Aotearoa New Zealand, a national Symposium on Cultural Competence and Māori Health, convened by the Medical Council of New Zealand and Te Ohu Rata o Aotearoa - Māori Medical Practitioners Association (Te ORA) and consultation with Māori medical practitioners via Te ORA. Results Health practitioners, healthcare organisations and health systems need to be engaged in working towards cultural safety and critical consciousness. To do this, they must be prepared to critique the 'taken for granted' power structures and be prepared to challenge their own culture and cultural systems rather than prioritise becoming 'competent' in the cultures of others. The objective of cultural safety activities also needs to be clearly linked to achieving health equity. Healthcare organisations and authorities need to be held accountable for providing culturally safe care, as defined by patients and their communities, and as measured through progress towards achieving health equity. Conclusions A move to cultural safety rather than cultural competency is recommended. We propose a definition for cultural safety that we believe to be more fit for purpose in achieving health equity, and clarify the essential principles and practical steps to operationalise this approach in healthcare organisations and workforce development. The unintended consequences of a narrow or limited understanding of cultural competency are discussed, along with recommendations for how a broader conceptualisation of these terms is important.